2021
DOI: 10.3390/nano11030806
|View full text |Cite
|
Sign up to set email alerts
|

Combined Toxicity of Gas Plasma Treatment and Nanoparticles Exposure in Melanoma Cells In Vitro

Abstract: Despite continuous advances in therapy, cancer remains a deadly disease. Over the past years, gas plasma technology emerged as a novel tool to target tumors, especially skin. Another promising anticancer approach are nanoparticles. Since combination therapies are becoming increasingly relevant in oncology, both gas plasma treatment and nanoparticle exposure were combined. A series of nanoparticles were investigated in parallel, namely, silica, silver, iron oxide, cerium oxide, titanium oxide, and iron-doped ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 60 publications
(60 reference statements)
1
11
0
Order By: Relevance
“…In the last few years, the combination therapy with CAP and other treatments has claimed that may promise cure of cancer [15,[29][30][31][32][38][39][40][41][42]. This study revealed that CAP had more cytotoxic effect on tumor cells and did not have a toxic effect on normal cells.…”
Section: Discussionmentioning
confidence: 93%
“…In the last few years, the combination therapy with CAP and other treatments has claimed that may promise cure of cancer [15,[29][30][31][32][38][39][40][41][42]. This study revealed that CAP had more cytotoxic effect on tumor cells and did not have a toxic effect on normal cells.…”
Section: Discussionmentioning
confidence: 93%
“…Of those, RONS are hypothesized to mediate the effects observed in biological systems as they are known to be involved in rapid reactions with important biomolecules such as proteins, lipids, and nucleic acids [ 21 , 33 , 34 ]. In recent years, multiple studies have shown that plasma is able to effectively kill many types of cancer cells via different cell death mechanisms, including melanoma [ [35] , [36] , [37] , [38] , [39] ]. NTP can exert its biomedical effects either by direct treatment of cancer cells or by indirect treatment, i.e., by applying NTP-treated solutions, rich in long-lived reactive species [ 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar results for melanoma were obtained when gas plasmas and NPs were used together. The increase of ROS/RNS resulting from the combination of different configurations of gas plasma with FAK antibody conjugated-AuNPs, silica, silver, iron oxide, cerium oxide, titanium oxide, iron-doped titanium oxide NPs, and Anti-EGFR-AuNPs leads to a significant increase of early apoptosis and secondary necrosis, reduction in G2/M levels, increase in the sub-G1 fraction, FAS externalization, caspase-8 activation, increase of selective cancer cell death, inhibition the viability of cancer cells, and reduction of growth pattern [163][164][165][166][167].…”
Section: Relationship Between Reactivity and Therapeuticmentioning
confidence: 99%
“…Lung cancer [249] Silica, silver, iron oxide, cerium oxide, titanium oxide, and irondoped titanium oxide NPs, and plasma jet (i) Reduction of growth pattern (ii) Increased cytotoxic effects (iii) ROS/RNS generation Melanoma [166] AuNPs and plasma jet (i) Increase of apoptotic cell death (ii) Induction of nuclear condensation and DNA fragmentation…”
Section: Challenges To Achieving Clinical Success and Futurementioning
confidence: 99%